2013
DOI: 10.3390/su5093876
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduced Tillage on Crop Yield, Plant Available Nutrients and Soil Organic Matter in a 12-Year Long-Term Trial under Organic Management

Abstract: A field experiment was performed in Southwest Germany to examine the effects of long-term reduced tillage (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012). Tillage treatments were deep moldboard plow: DP, 25 cm; double-layer plow; DLP, 15 + 10 cm, shallow moldboard plow: SP, 15 cm and chisel plow: CP, 15 cm, each of them with or without preceding stubble tillage. The mean yields of a typical eight-year crop rotation were 22% lower with CP compared to DP, and 3% lower with SP and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 42 publications
0
29
0
1
Order By: Relevance
“…Recent results indicate that deficiencies in plant-available N can be compensated for by planting legume cover crops, like common vetch (Vicia sativa L.), prior to growing a cereal cash crop [59]. For soil parameters, the German long-term trials confirm the benefits of RT and NT in organic farming which have been found elsewhere (e.g., [60]): higher earthworm biomass [61], enrichment of soil organic matter in the top soil [62] or even to deeper soil horizons [16], higher microbial respiration [57], higher microbial carbon and aggregate stability in the top soil [17,62].…”
Section: Trial Resultsmentioning
confidence: 49%
See 3 more Smart Citations
“…Recent results indicate that deficiencies in plant-available N can be compensated for by planting legume cover crops, like common vetch (Vicia sativa L.), prior to growing a cereal cash crop [59]. For soil parameters, the German long-term trials confirm the benefits of RT and NT in organic farming which have been found elsewhere (e.g., [60]): higher earthworm biomass [61], enrichment of soil organic matter in the top soil [62] or even to deeper soil horizons [16], higher microbial respiration [57], higher microbial carbon and aggregate stability in the top soil [17,62].…”
Section: Trial Resultsmentioning
confidence: 49%
“…In most of the trials, the high weed pressure in the treatments with shallow, non-inversion tillage was described as the main reason for yield reduction, while skimmer plough treatments and double layer plough treatments often performed similarly to the moldboard plough [16,47]. Weeds having the greatest impact on yield were perennial weeds like C. arvense L. [13], and direct seeding resulted in complete yield loss of the cash crop in some years due to excessive weed pressure [59].…”
Section: Trial Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…E. P. Zikeli et al (2013) [18] showed that the reduction of intensity and depth of tillage improves SOM contents in a Germany Luvisol. Use of NT resulted in positive effects on SOM in subtropical and tropical soils (Conceição et al, 2013) [9].…”
Section: Resultsmentioning
confidence: 99%